Proceedings of the 6th International Conference on Strategies, Models and Technologies of Economic Systems Management (SMTESM 2 2019
DOI: 10.2991/smtesm-19.2019.75
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrency portfolio optimization using Value-at-Risk measure

Abstract: Current research has led to a rejection of the hypothesis of a normal distribution of financial assets returns. Under these conditions, portfolio variance cannot serve as a good risk measure. In this paper analyzed the daily returns of the most common cryptocurrencies: Bitcoin, Bitcoin Cash, Litecoin, XRP, Ethereum, NEM. It is shown that the asset returns are not normally distributed, but with good precision follow the Cauchy distribution. The analytical expressions for risk measure were obtained using the Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…The proposed algorithm displayed good performance in estimating both VaR and ES. Hrytsiuk et al (2019) showed that the cryptocurrency returns can be described by the Cauchy distribution and obtained the analytical expressions for VaR risk measures and performed calculations accordingly. As a result of the optimisation, the sets of optimal cryptocurrency portfolios were built in their experiments.…”
Section: Crypto-asset Portfolio Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed algorithm displayed good performance in estimating both VaR and ES. Hrytsiuk et al (2019) showed that the cryptocurrency returns can be described by the Cauchy distribution and obtained the analytical expressions for VaR risk measures and performed calculations accordingly. As a result of the optimisation, the sets of optimal cryptocurrency portfolios were built in their experiments.…”
Section: Crypto-asset Portfolio Researchmentioning
confidence: 99%
“…tions and major feature engineering have the potential to further improve the predictive power. More Intelligent Evolutionary Optimisation (IEO) for hyperparameter optimisation is core problem when tuning the overall optimization process of machine learning models(Huan et al 2020). Lu et al (2020) proposed a CNN-LSTM based method for stock price prediction.…”
mentioning
confidence: 99%
“…: Sefiane i Benbouziane, 2012; Škarica i Lukač, 2012; Tarczyński, 2014; Gluzicka, 2016; Goudarzi et. al., 2017;Hrytsiuk et al, 2019;Mercurio et. al., 2020).…”
Section: Wstępmentioning
confidence: 99%
“…naive strategy, classical Markowitz model and its modifications, optimization strategies taking into account e. g. the value at risk, the diversification level, taxonomic measures of investment attractiveness or investment strategies based on different methods of computational intelligence, such as genetic algorithms or hybrid models (see for example: Sefiane and Benbouziane, 2012; Škarica and Lukač, 2012;Tarczyński, 2014;Gluzicka, 2016;Goudarzi et. al., 2017;Hrytsiuk, 2019;Mercurio et. al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed algorithm displayed good performance in estimating both VaR and ES. Hrytsiuk et al [123] showed that the cryptocurrency returns can be described by the Cauchy distribution and obtained the analytical expressions for VaR risk measures and performed calculations accordingly. As a result of the optimisation, the sets of optimal cryptocurrency portfolios were built in their experiments.…”
Section: Crypto-asset Portfolio Researchmentioning
confidence: 99%